ChemInform Abstract: Pd‐Catalyzed Ethylene Methoxycarbonylation with Broensted Acid Ionic Liquids as Promoter and Phase‐Separable Reaction Media. Issue 18 (17th April 2014) - Garcia‐Suarez, Eduardo J.; Khokarale, Santosh G.; van Buu, Olivier N.; Fehrmann, Rasmus; Riisager, Anders
Abstract: Preformation of the catalytic system by stirring the ionic liquid with Pd(OAc)2 and a ligand in MeOH is important to avoid the formation of Pd‐black and thus to improve the reusability of the catalyst system up to 15 recycle experiments without decrease of the conversion.